Stride parameters and modifications in sprint training - Paruzel-Dyja, M. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Among many stride parameters, stride length and frequency are believed to be sprint velocity determinants. According to many authors (eg. Jarver 2004) speed is a function of stride length and frequency, and faster speeds are achieved when one or both of the stride variables increase. One has to remember that these parameters are in close relation, what means that while one of them increases the other often decreases, however it is important to find an optimal balance between them. The aim of the study was to evaluate the changes of running stride parameters of elite Polish sprinters in different periods of the annual training cycle, in the context of training program modification.